Obtenção de nova superfície seletiva usando compósitos à base de óxidos de cromo, ferro e alumínio para coletores solares térmicos - Dutra, Kaio Hemerson (2022)
The depletion of fossil fuels and the concern for their environmental impacts encourages research for other energy sources. In this context, solar energy presents itself in a promising way, due to its availability and applicability, especially in thermal processes. However, its use still represents a technological and economic challenge. As a result, the search for process improvement arouses research into more efficient and alternative materials and manufacturing processes. In solar collectors, to maximize the absorbed energy, selective surfaces deposited on the fins are used, their use significantly improves the performance of these equipments. This work has the general objective of developing a methodology for the fabrication of a new composite selective surface for use in solar thermal collectors from the use of chromium, iron and aluminum oxides, as well as to carry out its characterization and evaluation of its performance in tests of field. To obtain the selective surfaces, evaluations of granulometry, fondant, binding and thermal treatments were carried out, so that adequate surfaces with good adhesion to the metallic substrate could be obtained. Field tests were carried out with sun exposure, assessment of the photodegradation and characterization. In the characterization, scanning electron microscopy (SEM) and infrared and UV-VIS spectrophotometer were used. The tests guided the production process of the new composite by indicating the best manufacturing parameters, making it possible to obtain five surfaces with varying compositions of aluminum oxide (Al2O3) and iron-chromium oxides (CRFO). The results showed the selective surface with 25% Al2O3 + 75%CRFO as the one with the best performance, reaching a maximum temperature of 75.7°C and measured absorptivity of 0.957, followed by the commercial reference surface that reached a maximum temperature of 74.7°C and absorptivity of 0.95, the other surfaces presented inferior performance. It was possible to conclude, by the tests and characterizations carried out, that the surface obtained by the manufacturing process developed in this work is an alternative for use in solar thermal collectors and presents better performance when compared to the commercial surface MRTiNOX.